2017
DOI: 10.1038/srep45132
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic infection of BrYV and PEMV 2 increases the accumulations of both BrYV and BrYV-derived siRNAs in Nicotiana benthamiana

Abstract: Viral synergism is caused by co-infection of two unrelated viruses, leading to more severe symptoms or increased titres of one or both viruses. Synergistic infection of phloem-restricted poleroviruses and umbraviruses has destructive effects on crop plants. The mechanism underlying this synergy remains elusive. In our study, synergism was observed in co-infections of a polerovirus Brassica yellows virus (BrYV) and an umbravirus Pea enation mosaic virus 2 (PEMV 2) on Nicotiana benthamiana, which led to (1) incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…It has been also previously demonstrated that DCL4 can downregulate DCL2 expression [56]. [66]. These results are in agreement with our previous findings [51,54] It should take in account, however, that ours results to not exclude that other CLRDV-resistance mechanisms not directly related to DCL2/4 modulation should be active in DO plants.…”
Section: Discussion 14supporting
confidence: 93%
“…It has been also previously demonstrated that DCL4 can downregulate DCL2 expression [56]. [66]. These results are in agreement with our previous findings [51,54] It should take in account, however, that ours results to not exclude that other CLRDV-resistance mechanisms not directly related to DCL2/4 modulation should be active in DO plants.…”
Section: Discussion 14supporting
confidence: 93%
“…Brassica yellows virus (BrYV) is a tentative species in the genus Polerovirus . Viruses in this genus and Luteovirus are limited to the phloem and transmitted by aphid ( King et al, 2012 ; Zhou et al, 2017 ). BrYV is distributed widely in mainland China, as well as in South Korea and Japan ( Xiang et al, 2011 ; Zhang et al, 2014 ; Lim et al, 2015 ; Kamitani et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For convenience of the virus research, the full-length infectious cDNA clones of BrYVs were constructed under control of the cauliflower mosaic virus 35S promoter ( Zhang et al, 2015 ). As the BrYV is a phloem-restricted virus, an umbravirus Pea enation mosaic virus 2 (PEMV 2) can help BrYV to be mechanically transmitted and invade non-vascular tissue in Nicotiana benthamiana ( Zhou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is assumed that DCL2 and DCL4 likely play important role in generating WLYaV siRNAs whereas in most viruses and viroids, the 21 nt species is the predominant class (Donaire et al, 2009 ; Ma et al, 2011 ; Li et al, 2012 ; Zhang et al, 2014 ). For poleroviruses such as cotton leafroll dwarf virus, MaYMV, and brassica yellows virus, the abundant vsiRNA class is 22 nt (Silva et al, 2011 ; Chen et al, 2016 ; Zhou et al, 2017 ). This suggests that these poleroviruses and WLYaV may affect DCL4 activity which is then compensated by DCL2.…”
Section: Discussionmentioning
confidence: 99%